Reproductive health knowledge among college students in Kenya - Samuel Mungai Mbugua; Jane Muthoni Karonjo (BMC, 2018)
Abstract Background Reproductive health knowledge is vital in the growth and development of young people and this impact greatly on their educational and personal outcome as they proceed to adulthood. There has been an increasing occurrence of sexually transmitted infections in institutions of higher learning. The study sought out the strategies used by university students to prevent unplanned pregnancy and determined their knowledge of contraception methods and sexually transmitted infections in Mount Kenya University, main campus. Methods Stratified sampling was employed. After a signed consent was obtained, a self-administered questionnaire was used to collect data. Data were explored, analyzed and percentages used to quantify the level of knowledge. Pearson's chi-square was used to measure associations between categorical variables and independent t-test used to measure the means and relationships of continuous variables. Results Condom use was established as the most prevalent strategy in prevention of unplanned pregnancy at 48.5 and 46.4% in prevention of STI and HIV/AIDS. Almost two thirds (58%) of respondents reported that they were conversant with only one method of contraception, 60% had knowledge of more than two types of STIs, and 62.4% indicated that they were conversant with only hospitals as facilities providing reproductive health services. Conclusion Young people in college require educational initiatives to sensitize them on STI, methods of contraception and positive social behaviors. There is need to improve the accessibility of reproductive health services through strengthening of services provided at campus health clinics.